Szkoły polonijne we Włoszech. Aktywność edukacyjno-szkoleniowa nauczycielek polonijnych zrzeszonych w ROP - Barańska , Magdalena (Studia Edukacyjne, 2023)
The activities of Polish community schools are significant and rich in various initiatives promoting broadly understood Polishness. This is an area that has yet to be explored empirically. There are few scientific studies dealing with the functioning of Polish community schools in specific countries, describing the difficulties and challenges teachers are coping with while characterizing their potential and possibilities. Polish community education has evolved over the last few years. As a result of social and cultural changes, and the dynamics of migration processes, it must re-profile itself and start meeting the needs of children, both those who speak Polish and those who do not know Polish at all, and the implementation of this task belongs to Polish community teachers in Italy.